2019
DOI: 10.1038/s41598-019-54480-9
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol delivery during invasive mechanical ventilation: development of a preclinical ex vivo respiratory model for aerosol regional deposition

Abstract: In intensive care units, nebulization is a usual route for drug administration to patients under mechanical ventilation (MV). The effectiveness of inhalation devices as well as depositions sites of aerosols for ventilated patients remain poorly documented. In vivo human inhalation studies are scarce due to ethical restrictions because imaging techniques require radioaerosols to assess regional aerosol deposition. Thus, we developed an ex vivo respiratory model under invasive MV for preclinical aerosol depositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…To reach this objective, innovative ex vivo respiratory models appear to be an interesting preclinical tool to assess aerosol regional deposition of nano-delivery systems in healthy and pathological-like respiratory tracts [165,201]. Composed of a 3D-printed Ear-Nose-Throat replica connected to ex vivo animal respiratory tract in a hypobaric chamber simulating passive ventilation, these models appear as an innovative and promising way to quantitatively assess aerosol deposition into the lungs and to transpose it more easily to human [202,203].…”
Section: Beyond In Vivo Animal Experiments the Need To Develop Innova...mentioning
confidence: 99%
“…To reach this objective, innovative ex vivo respiratory models appear to be an interesting preclinical tool to assess aerosol regional deposition of nano-delivery systems in healthy and pathological-like respiratory tracts [165,201]. Composed of a 3D-printed Ear-Nose-Throat replica connected to ex vivo animal respiratory tract in a hypobaric chamber simulating passive ventilation, these models appear as an innovative and promising way to quantitatively assess aerosol deposition into the lungs and to transpose it more easily to human [202,203].…”
Section: Beyond In Vivo Animal Experiments the Need To Develop Innova...mentioning
confidence: 99%
“…Nevertheless, a difference arose in our results for RT distribution when the position upstream HH and dry condition interacts. Indeed, these parameters (condition D-1) allowed a more peripheral deposition compared to each other condition, as previously described (25). However, this nding must be rst balanced with an absolute RT deposited fraction lower than other conditions and then with the risks for patients when interrupting the humidi cation for nebulization.…”
Section: Impact Of Humidi Cationmentioning
confidence: 78%
“…Mechanical ventilation (MV) largely impacts the aerosolization efficiency and deposition within the respiratory tracts of the pulmonary delivered siRNA/siRNA carriers 83 , 84 . Harmfully, the presence of heat and humidity in the ventilator circuit can reduce the efficiency of drug delivery 83 .…”
Section: Pulmonary Delivery Of Sirna For Treatment Of Ali/ards: Advantages and Barriersmentioning
confidence: 99%
“…In patients receiving mechanical ventilation, it is difficult to ensure that the aerosolized particles are efficiently delivered to distal airways 85 . It has been reported that the aerosol generated by nebulizers in mechanically ventilated patients was mostly deposited in proximal airways with a lung deposition lower than 20% of the nominal dose 84 , 86 . Thus, inhalation devices and administration procedures have to be improved for patients under MV 84 .…”
Section: Pulmonary Delivery Of Sirna For Treatment Of Ali/ards: Advantages and Barriersmentioning
confidence: 99%
See 1 more Smart Citation